Probing the evolution of appendage specialization by Hox gene misexpression in an emerging model crustacean - Pavlopoulos, Anastasios (National Academy of Sciences, 2009)
Changes in the expression of Hox genes have been widely linked to the evolution of animal body plans, but functional demonstrations of this relationship have been impeded by the lack of suitable model organisms. A classic case study involves the repeated evolution of specialized feeding appendages, called maxillipeds, from anterior thoracic legs, in many crustacean lineages. These leg-to-maxilliped transformations correlate with the loss of Ultrabithorax (Ubx) expression from corresponding segments, which is proposed to be the underlying genetic cause. To functionally test this hypothesis, we establish tools for conditional misexpression and use these to misexpress Ubx in the crustacean Parhyale hawaiensis. Ectopic Ubx leads to homeotic transformations of anterior appendages toward more posterior thoracic fates, including maxilliped-to-leg transformations, confirming the capacity of Ubx to control thoracic (leg) versus gnathal (feeding) segmental identities. We find that maxillipeds not only are specified in the absence of Ubx, but also can develop in the presence of low/transient Ubx expression. Our findings suggest a path for the gradual evolutionary transition from thoracic legs to maxillipeds, in which stepwise changes in Hox gene expression have brought about this striking morphological and functional transformation.